2021
DOI: 10.21834/ebpj.v6i16.2707
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Experience with and Connectedness to Nature Among Children

Abstract: This study aims to identify the age and gender differences in children's experiences with nature and their connectedness to nature (CTN). This study employed a quantitative approach and involved 760 children aged 10-11 years old, including urban and rural children in Kedah and Pulau Pinang. Questionnaires were distributed to children at schools. Findings suggest that age and gender do influence the frequency of children having experiences with nature as well as their CTN. The directions for future research are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Differences in scores on nature connectedness have also been reported when it comes to both age and gender. In children it has been found that girls are more connected than males, despite boys reporting having more contact with nature ( Mustapa et al , 2021 ). Among adult student samples no gender differences were found, however some personality factors, which may have developed over time and into adulthood, may be responsible for this change ( Di Fabio & Rosen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in scores on nature connectedness have also been reported when it comes to both age and gender. In children it has been found that girls are more connected than males, despite boys reporting having more contact with nature ( Mustapa et al , 2021 ). Among adult student samples no gender differences were found, however some personality factors, which may have developed over time and into adulthood, may be responsible for this change ( Di Fabio & Rosen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%